PENGEMBANGAN INVENTORI WELLNESS EVALUATION OF LIFESTYLE (WEL) UNTUK REMAJA - Isnaini, Rohmatus; Ayuningtyas, Ika; Suhendarto, Arif (Pelita - Jurnal Penelitian Mahasiswa UNY, 2015)
The objective of the research is to produce a Wellness Evaluation of Lifestyle (WEL) inventory for teenagers. The method is research and development by adapting the existing Wellness Evaluation of Lifestyle. The subjects of the research are 56 students of State Junior High School 9 Yogyakarta and State Senior High School 4 Yogyakarta. This reseacrh produces a Wellness Evaluation of Lifestyle (WEL) which meets the cultural condition, character, religion, and bahasa Indonesia. In the items of the Wellness Evaluation of Lifestyle (WEL) inventori there are 17 components of wellness from the Wheel of Wellness, namely 1) creativity and problem solving, 2) control feeling, 3) coping and emotional awareness, 4) senseof humour, 5) occupation, 6) spare time, 7) stress management, 8) feeling of deserving, 9) realistic belief, 10) friendship, 11) love, 12) spirituality, 13) self care, 14) gender identity, 15) cultural identity, 16) nutrition, dan 17) exercise, elaborated in the statements. In the Wellness Evaluation of Lifestyle (WEL) inventory in bahasa Indonesia there are 123 statements related to wellness and 6 additional questions. The validity testing in the development of WEL inventory uses an expert judgement and the reliability of the inventory which is 0.939 uses alpha cronbach 0.70 so the inventory can be used as a tool to identify the students' wellness as the basis for the guidance and counseling service.